Influence of goat colostrum and mature milk on intestinal microbiota. (November 2021) - Liu, Yufang; Cai, Junna; Zhang, Fuxin
Graphical abstract: Highlights: Ingestion of goat milk increased the microbial diversity of intestinal microbiota. Colostrum intake promote the growth of Lactobacillus and pathogen Helicobacter . Ingestion of mature milk increased the abundance of Lactobacillus and Muribaculum . Fat content were positively associated with the abundance of Helicobacter . Abstract: In this study, we compared the content of main components in goat colostrum and mature milk, and evaluated their influences on the intestinal microbiota to establish the correlations between milk components and functional features of the intestinal microbiota. Compared with goat mature milk, colostrum had significantly higher contents of protein, fat, minerals, dry matter, EGF, IGF-I, LTF and IgG, but lower concentrations of lactose and cAMP. The metagenomic analysis indicated that ingestion of mature milk increased the abundance of probiotic bacteria Lactobacillus and Muribaculum, while goat colostrum intake could promote the growth of probiotics Lactobacillus and Alistipes, but also the pathogen Helicobacter . Fat content was positively associated with the abundance of Helicobacter . Our study provided evidence that goat colostrum and mature milk could change the composition and structure of the intestinal microbiota community in different ways, which might drive the downstream effects on the host's metabolism and health.